2017
DOI: 10.1111/gcbb.12438
|View full text |Cite
|
Sign up to set email alerts
|

Oilseed rape (Brassica napus) as a resource for farmland insect pollinators: quantifying floral traits in conventional varieties and breeding systems

Abstract: Oilseed rape (OSR; Brassica napus L.) is a major crop in temperate regions and provides an important source of nutrition to many of the yield‐enhancing insect flower visitors that consume floral nectar. The manipulation of mechanisms that control various crop plant traits for the benefit of pollinators has been suggested in the bid to increase food security, but little is known about inherent floral trait expression in contemporary OSR varieties or the breeding systems used in OSR breeding programmes. We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 79 publications
2
35
0
Order By: Relevance
“…Bees may then preferentially visit fields of optimized varieties over less rewarding flowers in the environment, based on location cues. Similar possibilities for nectar production have also recently been shown in two other pollinator-dependent crops-sunflower and oilseed rape (Carruthers et al, 2017;Mallinger & Prasifka, 2017). We suggest for V. faba that this could be achieved most effectively by improving the pollen production and nectar sugar concentration of flowers (but not above 55% w/w), while maintaining an average volume of nectar in flowers.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Bees may then preferentially visit fields of optimized varieties over less rewarding flowers in the environment, based on location cues. Similar possibilities for nectar production have also recently been shown in two other pollinator-dependent crops-sunflower and oilseed rape (Carruthers et al, 2017;Mallinger & Prasifka, 2017). We suggest for V. faba that this could be achieved most effectively by improving the pollen production and nectar sugar concentration of flowers (but not above 55% w/w), while maintaining an average volume of nectar in flowers.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, optimal floral trait combinations to attract pollinators and maintain high pollination rates may have been lost by genetic drift or selective sweeps. This has led to the suggestion that breeding crops through selecting for floral traits could lead to improvements in food security by attracting greater numbers of pollinators, as well as improving foraging resources for wild pollinator communities (e.g., Bailes, Ollerton, Pattrick, & Glover, 2015;Carruthers et al, 2017;Mallinger & Prasifka, 2017;Palmer, Perez, Ortiz-Perez, Maalouf, & Suso, 2009).…”
mentioning
confidence: 99%
“…The optimum pod number for maximum OSR yield is in the region of 6000-8000 pods/m 2 (Berry and Spink 2006). However, significantly more flowers than necessary for optimum pod number are usually produced, and the presence of these 'excess flowers' enables the crop to tolerate some pollen beetle-related flower loss before yields are reduced (Ellis and Berry 2012); excess flower numbers have been shown to vary according to cultivar (Ellis and Berry 2012;Carruthers et al 2017) and thus are likely to be important determinant of a particular cultivar's tolerance to pollen beetle attack. A recent study showed that, in general, cultivars bred using the cytoplasmic male-sterility (CMS) technique generally had more flowers than hybrids produced by genetic male-sterility (GMS) techniques and open-pollinated varieties (Carruthers et al 2017).…”
Section: Cultivarmentioning
confidence: 99%
“…Brassica napus (AACC, 2n = 38) is an allotetraploid oilseed plant species formed by the hybridization of two diploid species of Brassica rapa (AA,2n = 20) and Brassica oleracea (CC, 2n = 18) about 7,500 years ago (Chalhoub et al, 2014;An et al, 2019). It is the third largest oil crop in the world and accounts for approximately 15% of the vegetable oil used for human consumption (Wells et al, 2014;Liu et al, 2016;Carruthers et al, 2017;Kaur et al, 2019). Like most oilseeds, triacylglycerols (TAGs) comprise 95% of B. napus seed oil which are composed of a glycerol backbone esterified with three fatty acyl chains (Ai et al, 2014;Guan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%